Odpowiedzi

2010-02-12T22:47:20+01:00
A)
3x+y=5
2x-y=0
------------------- dodajemy
5x=5
x=1

2x-y=0
2-y=0
2=y

powinno wyjść x=1 y=2

b)
2x-y=5
x+y=4
------------------- dodajemy
3x=9
x=3

x+y=4
3+y=4
y=4-3
y=1

powinno wyjść x=3 y=1

c)
-x-y=-6
-x+y=2
-------------------dodajemy
-2x=-4 /*(-1)
2x=4
x=2

-x+y=2
-2+y=2
y=2+2
y=4

powinno wyjść x=2 y=4
d)
4x-5y=-4
-2x+3y=1,1 /*2

4x-5y=-4
-4x+6y=2,2
-------------------dodajemy
y=-1,8

-2x+3y=1,1
-2x+3(-1,8)=1,1
-2x-5,4=1,1
-2x=1,1+5,4
-2x=6,5
x=-3,25

powinno wyjść x=-3,25y y=-1,8
1 5 1
2010-02-12T22:47:26+01:00
1.
3x+y=5
2x-y=0
__________________ dodajemy równania
5x+0=5
x=1

3*1+y=5
y=5-3
y=2

x=1
y=2

2.
2x-y=5
x+y=4
__________
3x+0=9
x=3

3+y=4
y=4-3
y=1

x=3
y=1
1 1 1